A case of listeriosis with brain stem abscess and rhombencephalitis in a sheep farmer. Issue 2 (5th October 2013) - Kerton, Matthew; Shrikrishna, Dinesh; Innes, Richard; Fathers, Edward; Gibbs, Richard
Summary: We describe the management of a patient with listeria rhombencephalitis, a rare manifestation of listeriosis. The patient was admitted to the ICU following neurological deterioration and the development of respiratory failure. His treatment consisted of high dose amoxicilln, gentamicin and methylprednisolone. Despite prolonged mechanical ventilation, facilitated by tracheostomy insertion, he was discharged home after neurorehabilitation with independent functional status.